Inclusive Collaborative Training Model (Kolin) Through an Androgogy Approach in Improving the Competence of Islamic Boarding School Caregivers - Deden Sugandi; Elih Sudiapermana; Joni Rahmat (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study analyzes the competence level of Islamic boarding school caregivers in Kuda Pasir District, Cianjur Regency, focusing on student management, education, and development, as well as identifying challenges in managing student diversity inclusively. Using a qualitative phenomenological approach, data were collected through interviews, observations, and literature studies. The study assessed caregivers’ competencies across seven aspects: pedagogical, personality, professional, social, managerial, spiritual, and technological-digital. Findings reveal that caregivers possess strong pedagogical and religious foundations but face challenges in educational management, curriculum adaptation, and technology use. Major obstacles in inclusive education include limited resources, lack of understanding of students with special needs (ABK), and persistent stigma within pesantren. Additionally, flexible curriculum design, differentiated instruction, and supporting facilities remain inadequate. To address these issues, the Inclusive Collaborative Training Model (KOLIN) was developed, emphasizing collaboration among caregivers, educational institutions, communities, and religious organizations. Evaluation results indicate improvements in pedagogical, managerial, and technological competencies. This study contributes theoretically to the development of inclusive-collaborative training models and offers practical implications for caregivers, religious institutions, and policymakers to enhance the inclusiveness and competitiveness of Islamic boarding school education.